Low density polyethylene degrading fungi isolated from local dumpsite of shivamogga district - H.V, Sowmya; bellibatlu, Ramlingappa; M, Krishnappa; B, Thippeswamy (International Journal of Biological Research, 2014)
Objective: To isolate polyethylene degrading fungi from dumpsite soil and to screen the enzymes responsible for polyethylene degradation. Methods: Enrichment method was followed for isolation of fungi. Plate assay method was followed for screening of fungus for its capacity to degrade polyethylene. Degradation experiment was carried out using different types of polyethylene. Degradation was confirmed by weight loss, Scanning Electron Microscopy (SEM) and Fourier Transform Infra-Red (FTIR) studies. Enzymes responsible for polyethylene degradation were screened and their activity was measured by spectrophotometric method. Results: Fungus isolated was identified as Chaetomium globsum. Chaetomium globsum was able to degrade differently treated polyethylene which was confirmed by weight loss, SEM and FTIR studies. Lactase and Manganese peroxidase enzymes were responsible for degradation. Conclusion: From current investigation, it can be concluded that our isolated fungus Chaetomium globosum had the capacity to degrade polyethylene and it can be useful in solving the problem caused by polyethylene in the environment. Keywords: Polyethylene; Chaetomium globosum; Laccase; Manganese Peroxidase; Biodegradation.